Analytical Thinking Siswa Dengan Teknologi Digital - Maghfirah, Aprilla Rizki; Safira, Sitta; Sabaruddin, Sabaruddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Advances in digital technology are changing the paradigm of learning, especially in the development of students' analytical thinking skills. Applications of technology, such as complex conceptual visualization and interactive approaches, have a positive impact on the quality of learning. Technology capabilities support collaborative learning, adapt teaching methods to student learning styles, and create intelligent digital learning systems. In the development of analytical thinking capabilities, digital technology is not only a tool but also a potential partner, becoming a catalyst for expanding and deepening the learning process. Research using library methods shows that the integration of digital technology in education contributes to the development of students' analytical thinking skills. While digital technology provides the advantage of information access and dynamic learning experiences, the role of teachers and active guidance remains important. A deep understanding of these dynamics is needed to design contextual, adaptive, and relevant learning approaches in the digital age.